Early Tracheostomy versus Late Tracheostomy in Patients with Moderate-to-Severe Traumatic Brain Injury - Nadeem, Umar; Fatima, Tahreem; Farooq, Ayesha; Hassan, Umar; Ahmed, Arslan (Asian Journal of Neurosurgery, 2024)
Objective The aim of this article was to study the impact of early versus late tracheostomy on clinical outcomes of moderate-to-severe traumatic brain injury (TBI).Materials and Methods A retrospective cross-sectional study was conducted in the Neurosurgery Department, Mayo Hospital, Lahore, in which a sample size of 50 cases was calculated over a period of 6 months from January 1, 2022, to June 30, 2022. The included cases were patients who suffered from moderate-to-severe TBI, isolated TBI, needed elective ventilation, required intensive care unit (ICU) admission during their hospital stay, and were between the ages of 18 and 65 years. All the rest were excluded. A structured proforma was used by the physician to collect data after the informed consent of the patient. The results were computed and analyzed statistically using Statistical Package for Social Sciences, version 26.Results The median age of patients was 40 (interquartile [IQ] range 34) years and were predominantly male (72%). The most common mode of injury was road traffic accidents (58%). The median Glasgow Coma Scale (GCS) score at arrival was 8 (IQ range 6) and the most common pupillary light reflex at presentation was bilaterally equally responsive to light (68%). Neurologic deficits were mostly absent or cannot be assessed on presentation (86%) and in 38% of the cases multiple findings were noted on computed tomography (CT) scan while among single findings seen on CT scan, subdural hematoma was the most common (22%). Multiple regression analysis was done through two separate models using age, gender, mode of injury, presenting GCS score, number of CT-scan findings, number of days after endotracheal intubation after which tracheostomy was done, and the timing of tracheostomy (early vs. late) as predictors, and a significant relationship was noted between the timing of tracheostomy (early vs. late) and GCS at discharge (p = 0.001) as well as extended Glasgow Outcome Score (GOS) at discharge (p = 0.013).Conclusion This study suggests that moderate-to-severe TBIs are most common in middle-aged males and mostly involve road traffic accidents. In most cases, multiple CT-scan findings are seen as compared with a single predominant finding. In such patients, early tracheostomy is superior to late tracheostomy as it results in significantly better GCS and GOS scores at discharge as well as a decreased duration of mechanical ventilation and ICU stay.
Keywords: traumatic brain injury; early versus late tracheostomy; severe TBI; multiple CT scan findings; road traffic accident; high-energy brain trauma; brain